Adult safeguarding under the Care Act 2014. (24th September 2018) - Johnson, Katherine; Boland, Billy
Abstract : Summary: Safeguarding adults is everybody's business, and it is now standard practice for clinicians to undertake safeguarding training as part of their mandatory training in the UK. Nevertheless, safeguarding work is complex and can involve significant dilemmas for professionals. The Care Act 2014 has introduced a number of differences in the way safeguarding is approached, emphasising the overall well-being and choice of the patient rather than merely focusing on their safety. This paper sets out to illustrate evolving safeguarding demand and practice, and aid clinicians in protecting people at risk by describing how they can approach challenging presentations. Declaration of interest: None.